Estudo teórico-bioclimático da potencialidade de desenvolvimento do Aedes aegypti no estado do Rio Grande do Norte - Silva, Bruno Claytton Oliveira da (2009)
In the current climate of global public health there is the emergence of urban dengue, a disease regarded as acute infectious fever. The disease annually, has affected millions of people worldwide, mostly in the range of the intertropical globe. The disease's main vector in urban areas, the Aedes aegypti mosquito. Recent studies indicate that the distribution of the insect vector of dengue in the geographical area is directly tied to the behavior of environmental restrictions that area, especially among those, the air temperature and relative humidity. From that context, the work aims to estimate and spatializing, monthly, for each municipality in the state of Rio Grande do Norte, the potential of biophysical conditions conducive to the development of Aedes aegypti. Yet, made use of the following methodology: collection of epidemiological data and climatological, Normal climatological, descriptive statistics (measures of central tendency and scatter), uniform distribution, estimation geostatistics and sufer program, version 8.0. The results flagged for a behavior very heterogeneous, both in space and in time, in the case of the potential of biophysical conditions conducive to the development of Aedes aegypti in the state of Rio Grande do Norte. Still, he noted that there is a tendency for lifting the potential of development for the entire state, from the month of January, ending in the month of April mainly in central and western portions of the state. By contrast, there is the permanence of increased potential for development in the eastern portion of the state. The latter record maximum potential in the month of July, resulting probability of greater than 70% have been favorable conditions for the development of Aedes aegypti in that area. In the period between the months of August to December, it is small potential for development of Aedes aegypti in all parts of the state